THE IMPORTANCE OF THEMES IN THE WORKS OF UTKIR KHOSHIMOV - Usmonova, Sharifa Gulamovna (Educational Research in Universal Sciences, 2022)
This article tells the description of a theme in literature and its importance in stories. Furthermore, the article analysis the dominant themes in Utkir Khoshimov’s works.